2018
DOI: 10.3390/pathogens7010012
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Characterisation of Five Strains of Bovine Viral Diarrhoea Virus 1 (Subgenotype 1c)

Abstract: Bovine viral diarrhoea virus 1 (BVDV-1) is strongly associated with several important diseases of cattle, such as bovine respiratory disease, diarrhoea and haemoragic lesions. To date many subgenotypes have been reported for BVDV-1, currently ranging from subgenotype 1a to subgenotype 1u. While BVDV-1 has a world-wide distribution, the subgenotypes have a more restricted geographical distribution. As an example, BVDV-1 subgenotypes 1a and 1b are frequently detected in North America and Europe, while the subgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The previous study pointed out that BVDV-1a and BVDV-1c were mainly circulating in cattle population (yak, dairy cattle, and beef cattle) in China ( 37 ). In fact, BVDV-1c is by far the most commonly circulating in Australia, and BVDV-1c infected cattle with no overt respiratory signs commonly displayed transient pyrexia and leukopenia ( 42 ). In our study, BVDV-1c plays important roles in BVDV infection for newborn calves.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study pointed out that BVDV-1a and BVDV-1c were mainly circulating in cattle population (yak, dairy cattle, and beef cattle) in China ( 37 ). In fact, BVDV-1c is by far the most commonly circulating in Australia, and BVDV-1c infected cattle with no overt respiratory signs commonly displayed transient pyrexia and leukopenia ( 42 ). In our study, BVDV-1c plays important roles in BVDV infection for newborn calves.…”
Section: Discussionmentioning
confidence: 99%
“…The phylogenetic analysis demonstrated that this genome sequence clusters with other BVDV-1c isolates ( Figure 4 ). The 1c genotype is the most reported genotype in the Australian cattle population [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…BVDV variability were generally analyzed using different genomic regions such as 5'UTR [33], N PRO [34], E2 [35], NS2-3 [36] and NS5B [37] and the result is not comparable to each other. Time periods for sampling also has an effect on the result of BVDV subgenotyping [28].Factor that influence the spread of the BVDV sub genotypes is unclear and do not appear to be affected by vaccine used but rather in part reflect the antigen diversity between strains [38]. According to [29], the genetic variation of the BVDV in a given geographic area has been largely influenced by animal movement within countries and/or introduction from other countries.…”
Section: Discussionmentioning
confidence: 99%